DKK3’s protective role in prostate cancer is partly due to the modulation of immune-related pathways - Shareef, Zainab Al; Hachim, Mahmood Y.; Talaat, Iman M.; Bhamidimarri, Poorna Manasa; Ershaid, Mai Nidal Asad; Ilce, Burcu Yener; Venkatachalam, Thenmozhi; Eltayeb, Abdulla; Hamoudi, Rifat; Hachim, Ibrahim Y. (Frontiers in Immunology, 2023)
While it is considered one of the most common cancers and the leading cause of death in men worldwide, prognostic stratification and treatment modalities are still limited for patients with prostate cancer (PCa). Recently, the introduction of genomic profiling, as well as, the use of new techniques like next-generation sequencing (NGS) in many cancers provides novel tools for the discovery of new molecular targets that might improve our understanding of the genomic aberrations in PCa and the discovery of novel prognostic and therapeutic targets. In this study, we investigated the possible mechanisms through which Dickkopf-3 (DKK3) produces its possible protective role in prostate cancer using NGS in both the DKK3 overexpression PCa cell line (PC3) model, as well as, our patients’ cohort consisting of 9 prostate cancer and 5 benign prostatic hyperplasia. Interestingly, our results have shown that DKK3 transfection-modulated genes are involved in the regulation of cell motility, senescence-associated secretory phenotype (SASP), and cytokine signaling in the immune system, as well as, in the regulation of adaptive immune response. Further analysis of our NGS using our in vitro model revealed the presence of 36 differentially expressed genes between DKK3 transfected cells and PC3 empty vector. In addition, both CP and ACE2 genes were differentially expressed not only between the transfected and empty group but also between the transfected and mock cells. The top common differentially expressed genes (DEGs) between the DKK3 overexpression cell line and in our patients’ cohort showed the list of the following; IL32, IRAK1, RIOK1, HIST1H2BB, SNORA31, AKR1B1, ACE2 and CP. The upregulated genes including IL32, HIST1H2BB and SNORA31 showed tumor suppressor functions in various cancers including PCa. On the other hand, both IRAK1 and RIOK1 were downregulated and involved in tumor initiation, tumor progression, poor outcome and radiotherapy resistance. Together, our results highlighted the possible role of the DKK3 related genes in protecting against PCa initiation and progression.